Micro, Small, and Medium Enterprises Based on Creative Economy Increasing the Competitiveness Excellence of The Modern Night Market Perdanaria Jakarta - Priyono Joko Alam; Lela Nurlaela Wati; Peggy Ratna Marlianingrum (Research Synergy Foundation, 2024)
Micro, small, and medium enterprises, especially those based on a creative economy, contribute to productive employment because they do not require specific requirements such as gender, education level, and capital, which are not defined using simple and easy-to-understand techniques. The creative economy in October 2021 contributed 7.8% of GDP and in 2022 targets US 25.14 billion. Creative economy-based MSMEs are an embodiment of optimism and positive aspirations in supporting and realizing the vision of an advanced Indonesia. The aim of this research was to analyze the competitive advantages of the Perdanaria Jakarta Modern Night Market. This study uses a qualitative approach with in-depth observation. The data used in this study are primary data obtained through structured interviews with micros mall medium enterprises based on creative economy, the management and crew of the Perdanaria Jakarta Modern Night Market. Based on observations and interviews with the owner of the Perdanaria Jakarta Modern Night Market, it can be seen that creative economy-based MSMEs have implemented their activities with creative and innovative ideas in presenting their products and marketing to attract and arouse consumer tastes with various models (fashion), flavors and variants (culinary) and fine arts. The results of this study can be generalized to other creative economies.